2023
DOI: 10.3390/microorganisms11061534
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-Related and Infection Control Approaches to Primary and Secondary Prevention of Clostridioides difficile Infections

Abstract: Clostridioides difficile infections (CDIs) have decreased in the past years, but since 2021, some hospitals have reported an increase in CDI rates. CDI remains a global concern and has been identified as an urgent threat to healthcare. Although multiple treatment options are available, prevention strategies are more limited. As CDI is an opportunistic infection that arises after the normally protective microbiome has been disrupted, preventive measures aimed at restoring the microbiome have been tested. Our ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
(221 reference statements)
0
4
0
Order By: Relevance
“…Innovative methods for preventing CDI are emerging. Prior studies have shown that probiotics and prebiotics can be effective in preventing CDI, particularly in high-risk groups [ 78 , 79 ]. Specifically, certain bacteria like Bacillus clausii and Lactobacillus reuteri are of interest because they produce substances that directly inhibit C. difficile [ 80 , 81 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Innovative methods for preventing CDI are emerging. Prior studies have shown that probiotics and prebiotics can be effective in preventing CDI, particularly in high-risk groups [ 78 , 79 ]. Specifically, certain bacteria like Bacillus clausii and Lactobacillus reuteri are of interest because they produce substances that directly inhibit C. difficile [ 80 , 81 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Probiotics in the Prevention of rCDI rCDI is defined as the recurrence of symptoms accompanied by a positive test for C. difficile toxin within 8 weeks of the preceding CDI episode [14]. The reported incidence of rCDI ranges between 15% and 20% [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research initially focused on effective treatments for CDIs and, as more CDI outbreaks occurred, better strategies to control healthcare-associated outbreaks in hospitals [4]. During the last two decades, the roles of various toxins, risk factors, and the importance of the protective intestinal microbiome have been established [4]. The development of newer tools has expanded the scope of research into the field of genomic expression of virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…A greater understanding of the pathogenesis cascade has led to strategies for the prevention and treatment of CDIs based on direct killing of the C. difficile bacterium with antibiotics or methods to restore the protective intestinal Antibiotics 2024, 13, 365 2 of 14 microbiome using probiotics or fecal microbial replacement. However, CDIs remain a global problem, and more innovative strategies to treat CDIs are urgently needed [4,5].…”
Section: Introductionmentioning
confidence: 99%